1997
DOI: 10.1097/00007632-199707010-00023
|View full text |Cite
|
Sign up to set email alerts
|

A System for Reporting the Size and Location of Lesions in the Spine

Abstract: The authors of the present study believe that all health care professionals who care for the spine will find this nomenclature valuable in communicating with each other, in writing medical reports, in presenting reports at meetings, or in writing scientific articles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 3 publications
0
37
0
3
Order By: Relevance
“…Using the classification by zones suggested by Wiltse et al 12 for our evaluation, we found no statistically significant correlation (p=0.902) between facet tropism and the location in the intervertebral disc where the disc herniation occurred. We believed that the greater the facet asymmetry (facet joint with a more coronal orientation), the greater the tendency towards more lateral disc herniation (foraminal or extraforaminal).…”
Section: Correlation Between Facet Tropism and The Location Of Thementioning
confidence: 57%
See 1 more Smart Citation
“…Using the classification by zones suggested by Wiltse et al 12 for our evaluation, we found no statistically significant correlation (p=0.902) between facet tropism and the location in the intervertebral disc where the disc herniation occurred. We believed that the greater the facet asymmetry (facet joint with a more coronal orientation), the greater the tendency towards more lateral disc herniation (foraminal or extraforaminal).…”
Section: Correlation Between Facet Tropism and The Location Of Thementioning
confidence: 57%
“…The anatomic location of the lumbar disc herniation in the axial plane, in relation to the location of the vertebral canal in which it occurred, was classified as central, central lateral, foraminal, and extraforaminal, according to the classification proposed by Wiltse et al 12 For this definition, axial cuts of the T1-and T2-weighted MRI exam were used.…”
Section: Methodsmentioning
confidence: 99%
“…The Wiltse system for reporting the size and location of lesions in the spine was implemented. 13 On the sagittal plane we defined superior, middle, and inferior locations for the vertebral segment. The superior area was equivalent to the suprapedicle and the pedicle level according to Wiltse system, while the middle area was equivalent to the infrapedicle level, and the inferior area was equivalent to the disc level according to the Wiltse system.…”
Section: Methodsmentioning
confidence: 99%
“…8,22 Caudally migrated fragments seem to be more impacted within the root axilla, might be more difficult to remove as the root is tented and fixed on the fragment. Thus, the initial root mobilization is not only difficult but extremely hazardous, and therefore initial generous foraminotomy should be completed before attempting to mobilize the root or address the fragment.…”
mentioning
confidence: 99%